Pendampingan Analisis Lapangan dalam Persiapan Pembentukan Program Bumdes di Desa Argosari, Sedayu, Bantul - Agustinus Hary Setyawan; Heribertus Binawan (Jurnal Pengabdian Pada Masyarakat, 2021)
FIELD ANALYSIS ASSISTANCE IN BUMDES PROGRAM PREPARATION IN ARGOSARI VILLAGE, SEDAYU, BANTUL. Argosari Village which is a potential village in the Sedayu, Bantul which is close to development trend currently because the New Yogyakarta International Airport has faced a problem to prepare recommendations for existing potentials as the embryo of Village-Owned Enterprises (BUMDes) activity units. Because of this urgency, an assistance is needed in preparing the BUMDes by analyzing the strengths, weaknesses, opportunities and threats of the potential units in the village. The implementation of this service is focused on the BUMDes formulation team by involving community leaders in each “dusun” who are related to the potential of Argosari Village. Assistance for the formation of BUMDes was carried out several times, each consisting of 2 stages. The stages of each cycle are: 1. The stage of extracting the village's potential, 2. The stage of mentoring with regular meetings to analyze field data. The results of field studies and regular coordination with the BUMDes formulation team obtained recommendations for several sectors to be raised in the Argosari BUMDes program which includes the tourism sector, waste management sector, culinary sector and bird cage crafts sector. These sectors will become embryonic priorities for the Argosari BUMDes business unit in the future.